1999
DOI: 10.1037/0012-1649.35.1.113
|View full text |Cite
|
Sign up to set email alerts
|

On facts and conceptual systems: Young children's integration of their understandings of germs and contagion.

Abstract: Five studies argue against claims that preschoolers understand a biological germ theory of illness. In Studies 1-3, participants were read stories in which characters develop symptoms (e.g., a bellyache) caused by germs, poisons, or events (e.g., eating too much candy) and were asked whether another character could catch the symptoms from the first. Few children made judgments in terms of germs as part of an underlying causal process linking the origin of a symptom to its subsequent transmission. Some children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
2
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 43 publications
3
71
2
5
Order By: Relevance
“…Les études sur la compréhension des maladies et de la santé ont longtemps été influencées par la théorie de Piaget sur le développement cognitif par étapes. En 1932, dans son ouvrage The moral Judgment of the Child (Solomon, 1999), Piaget montrait que les enfants s'attachaient souvent au comportement moral en décrivant les origines, les symptômes et même le traitement des maladies. Des enfants de moins de 9-10 ans expliquaient par exemple que la maladie pouvait être une punition à la suite d'une transgression morale, c'était le concept de « Justice immanente », repris par Bibace et Walsch (1980, cités dans Salomon 1999et dans Rushforth 1999.…”
Section: Les Capacités Cognitivesunclassified
See 1 more Smart Citation
“…Les études sur la compréhension des maladies et de la santé ont longtemps été influencées par la théorie de Piaget sur le développement cognitif par étapes. En 1932, dans son ouvrage The moral Judgment of the Child (Solomon, 1999), Piaget montrait que les enfants s'attachaient souvent au comportement moral en décrivant les origines, les symptômes et même le traitement des maladies. Des enfants de moins de 9-10 ans expliquaient par exemple que la maladie pouvait être une punition à la suite d'une transgression morale, c'était le concept de « Justice immanente », repris par Bibace et Walsch (1980, cités dans Salomon 1999et dans Rushforth 1999.…”
Section: Les Capacités Cognitivesunclassified
“…Sa position théorique a des implications pratiques auxquelles nous adhérons : le médecin et les soignants en général doivent pouvoir nouer avec les enfants une relation de confiance et de respect, qui va permettre à ceux-ci de comprendre dans une large mesure les explications et les concepts autour de la maladie qui les touche, eux ou leurs parents. Solomon et Cassimatis (1999) ne mettent pas en doute que les explications spontanées des jeunes enfants, surtout ceux de moins de 6-7 ans, font appel à la « Justice imma-99 nente » mais ils rapportent que, mis en présence d'un choix concernant la cause des maladies, les jeunes enfants optent plutôt pour le concept de « contagion » que pour celui de « Justice immanente ». Selon ces chercheurs, les enfants de moins de 6 ans :…”
Section: Les Capacités Cognitivesunclassified
“…More specifically, according to their findings children did not make different attributions of properties such as moving, eating, having babies, thinking and feeling sad to germs and poisons, while they did make different attributions of these properties to germs and animate beings such as people, ants and trees. Exploring further preschoolers' conceptualization of germs as living entities in another study, Solomon and Cassimatis (1999) found that only 17% of their informants made the attribution of 'eating' to germs, 0% made the attribution of 'growing' and 33% made the attribution of 'dying'. Considering these properties as central to reasoning about the 'living-nonliving' distinction, the findings of Solomon and Cassimatis (1999) indicate that most preschoolers did not think of germs as living entities.…”
mentioning
confidence: 97%
“…Exploring further preschoolers' conceptualization of germs as living entities in another study, Solomon and Cassimatis (1999) found that only 17% of their informants made the attribution of 'eating' to germs, 0% made the attribution of 'growing' and 33% made the attribution of 'dying'. Considering these properties as central to reasoning about the 'living-nonliving' distinction, the findings of Solomon and Cassimatis (1999) indicate that most preschoolers did not think of germs as living entities. In fact, they did not show for germs the pattern of inductive inference they showed for plants and animals.…”
mentioning
confidence: 97%
“…Indeed, instead of identifying germs as living organisms that multiply, American children aged 4-7 years appear to maintain that germs are not alive and that colds are as likely to be transmitted by poisons or by irritants such as pepper as by germs. They may also claim that germs grow like tumours but do not reproduce inside the body and do not eat or die [8].…”
Section: Knowledge Of Contamination and Contagion In Relation To Biolmentioning
confidence: 99%